Suzanne Lacy : spaces between - Irish, Sharon (University of Minnesota Press, 2010)
Often controversial and sometimes even shocking to audiences, the work of California-based artist Suzanne Lacy has challenged viewers and participants. Lacy has experimented with ways to claim the power of mass media, to use women's consciousness - raising groups as a performance structure, and to connect her projects to lived experiences. This book surveys Lacy's art from 1972 to the present, demonstrating the pivotal roles that Lacy has had in public art, feminist theory, and community organising.